Nursing professor as being-cared for in the professor-student relationship - Raúl Fernando Guerrero-Castañeda; Grever María Ávila Sansores; Sergio Albañil-Delgado (SciELO, 2022)
ABSTRACT Objective: to understand the meaning of professor as being-cared for that is manifested in the nursing professor-student relationship. Method: a qualitative phenomenological study, using Martin Heidegger's philosophical framework. It was carried out at a public university in Mexico. The phenomenological interview was used as a data collection method. An ontic analysis and a second analysis were carried out through Martin Heidegger's Hermeneutic circle. Results: within the interviews, 5 main themes were discovered, which were classified as: Care of physical needs, occupation as care; Nursing care teaching; Monitoring and coexisting with professors; Encouraging reflection on care towards authenticity; Students as a person, coexistence and existence of care. Conclusion: nursing professors, in addition to being the one who provides students with necessary knowledge for training nursing professionals, share aspects that involve more than science itself. Professors become a collaborator who hopes to contribute to nursing students' deepest aspects, impacting their academic training favorably.